MOLECULAR ADVANCES IN AUTOSOMAL DOMINANT POLYCYSTIC KIDNEY DISEASE - Gallagher, Anna Rachel (2010)
Autosomal dominant polycystic disease (ADPKD) is the most common form of inherited kidney disease that results renal failure. The understanding the pathogenesis of ADPKD has advanced significantly since the discovery of the two causative genes, PKD1 or PKD2. Dominantly inherited gene mutations followed by somatic second hit mutations inactivating the normal copy of the respective gene result in renal tubular cyst formation that deforms the kidney and eventually impairs its function. The respective gene products, polycystin-1 and polycystin-2, work together in a common cellular pathway. Polycystin-1, a large receptor molecule, forms a receptor-channel complex with polycystin-2, which is a cation channel belonging to the TRP family. Both polycystin proteins have been localized to the primary cilium, a non-motile microtubule based structure that extends from the apical membrane of tubular cells into the lumen. Here we discuss recent insights in the pathogenesis of ADPKD including the genetics of ADPKD, the properties of the respective polycystin proteins, the role of cilia, and some cell signaling pathways that have been implicated in the pathways related to PKD1 and PKD2.